Human-animal interaction as a social determinant of health: descriptive findings from the health and retirement study. - Mueller, Megan K.; Gee, Nancy R.; Bures, Regina M. (2018)
Background: We focused on human-animal interaction (HAI) as an important aspect of social functioning at the individual level, framing this emerging field from a public health perspective.; Keywords: Human-animal interaction, Companion animals, Aging.; Springer Open.